Shock-induced aggression as a function of prior experience with avoidance, fighting, or unavoidable shock - Powell, D. A. (1972)
Rats were trained in shock-induced aggression, free operant avoidance, or were presented with unavoidable shocks. Fighting in response to shock was subsequently measured by intermatching individual animals that had received the three training procedures. The fighting probabilities of animals with histories of avoidance and dominant animals with histories of fighting were higher than the fighting probabilities of non-dominant fighting rats or rats with a history of unavoidable shocks. Animals with higher fighting probabilities disrupted avoidance baselines more than animals with lower fighting probabilities. Control experiments suggested that fighting decrements produced by administration of prior grid-shock were due to the acquisition of behaviors incompatible with aggression.